Induction of Salt Stress Tolerance in Wheat Seeds by Parental Treatment with Salicylic Acid - Lei Yan; Xue Jiang; Yuman Zhang; Yongwen Dong; Can Zhao; Ke Xu; Zhongyang Huo; Weiling Wang (Plants)
Soil salinization is an important factor that limits crop production. The effects of spraying salicylic acid (SA) during the grain-filling stage on the salt tolerance of progeny seeds in wheat (Triticum aestivum L.) were investigated in this study. The results showed that spraying SA during the grain-filling stage significantly increased the grain weight and yield of wheat plants. Meanwhile, the seeds from the SA-treated plants showed a higher germination rate, length and dry mass of the coleoptile and radicle, and a lower mean germination time compared to the seeds of water-treated plants under the salt germination condition, indicating that SA pretreatment during the grain-filling stage could effectively improve the salt tolerance of progeny seeds in wheat. SA pretreatment significantly increased the activities of amylases and the respiration rate, accompanied by a decrease in starch content, and a higher accumulation in the level of soluble sugars and adenosine triphosphate (ATP) in the germinated seedlings compared to the water pretreatment under salt stress. In addition, SA pretreatment obviously alleviated the increase in malondialdehyde (MDA) content and the reactive oxygen species (ROS) release rate in seedlings by activating antioxidant enzymes (superoxide dismutase (SOD) and peroxidase (POD)) under salt stress. Moreover, the seedlings of the SA-treated plants showed lower Na+ and higher K+ contents compared to the seeds of water-treated plants under salt stress. The results of this study indicate that spraying SA during the grain-filling stage improves the capacity of offspring seeds to maintain osmotic and ion balance and redox homeostasis under salt stress, thereby conferring salt tolerance to the wheat seeds.